Digital Transformation In Regional Revenue Management: A Case Study At Bapenda Of East Java Province - Polrendyo Polrendyo; Ika Devy Pramudiana; Eny Haryati; Sri Kamariyah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Digital transformation in the public sector has become a strategic agenda to improve the efficiency, transparency, and quality of government services, including in regional revenue management. This study aims to analyze the implementation of digital transformation in the Regional Revenue Agency (Bapenda: Badan Pendapatan Daerah) of East Java Province, especially in the Gresik Technical Implementation Unit (UPT: Unit Pelaksana Teknis), as well as its impact on administrative efficiency, transparency, and increasing Regional Original Revenue (PAD: Pendapatan Asli Daerah). This study uses a non-empirical qualitative approach with a literature study method, which involves the analysis of secondary data from scientific journals, policy documents, government performance reports, and community digitalization indicators such as the Indonesian Digital Society Index (IMDI: Indeks Masyarakat Digital Indonesia). The results show that digital transformation through e-payment systems and web-based administration has significantly accelerated the service process, improved taxpayer compliance, and reduced revenue leakage. The receipt of PAD through digital channels increased by 60% in one year, while service efficiency increased by reducing administrative process time from three days to one day. The implementation of this digital transformation is also influenced by the readiness of infrastructure, apparatus competence, and community digital literacy, as described in the theoretical framework of the Technology Acceptance Model (TAM), Dynamic Capabilities, and TOE Framework. Despite positive achievements, challenges such as digital skills gaps, resistance to change, and system security issues are still obstacles in optimizing digital transformation. This research makes a theoretical contribution to the development of e-governance literature and digital public policy practices at the local level. These findings also provide concrete recommendations for other regions to replicate good practices of digital transformation that have succeeded in improving regional financial performance. Thus, digital transformation is not only a technological instrument, but also a governance strategy that requires synergy between technology, organizations, and society